ON THE DEVELOPMENT OF SPORTS EDUCATION FRAMEWORK IN MAASIN CITY, PHILIPPINES - Sarra, Jennifer C; Capili, Pritzel Lee G; Hungo, Melbert O; Casinillo, Leomarich F (IJIET (International Journal of Indonesian Education and Teaching), 2025)
The study focused on the crafting of a Sports Development Framework. A Delphi multi-survey was conducted with thirty (30) sports officers from Region VIII, who were selected as study participants through purposive sampling. Specifically, significant questionnaires and interviews were conducted during the first, second, third, and fourth rounds with the same participants. Consensus was reached in the fourth round, and findings were identified: Capacity building; Sports level competition; Community Impact; Project Management; Program specialization, Funding and resources; Training Facilities; Sports officers; Athletes' Performance; and Sports Benefits. It is concluded that a comprehensive approach to sports development involves various facets such as capacity building, competition levels, community impact, project management, and training facilities. Stakeholders, especially sports officers and community engagement, play a crucial role in successful initiatives while prioritizing athlete well-being and societal impacts. Hence, it is recommended to invest in capacity building for sports personnel, establish an inclusive competition structure, actively engage communities, implement effective project management systems, create specialized programs, ensure quality training facilities, and empower sports officers.